The molecular investigation of celiac disease - Rostami Nejad, Mohammad; Ahmadi, Naybali; Taherikalani, Morovat; Zali, Mohammad Reza (Archives of Advances in Biosciences, 2013)
Celiac disease (CD) is an immune-mediated disorder resulting in nutrient malabsorption now thought to have a prevalence of 1:100 in the Iranian population.Symptoms of CD are included diarrhea, abdominal pain, steatorrhea, bloating, cramps, flatulence, weight loss, weakness and short stature. In addition to presenting symptoms, patients are also at increased risk of metabolic bone disease, lymphoma (enteropathy-associated with T-cell) and other malignancies in different parts of the body such as gastric, esophageal, bladder, breast and brain. There appears to be a strong genetic component to this disease. In this short review we provided the historical, clinical and genetic aspects of this disease and highlight numerous findings from recent molecular immunology studies.